The Influence of Local Original Revenue (PAD), Balanced Funds, Budget Surplus (SILPA), and Special Allocation Funds (DAK) on Capital Expenditure (Case Study on Regency/City Governments in East Java 2017-2023) - Nabila Febriyana; Maulidah Narastri (International Journal of Economics, Commerce, and Management, 2025)
The purpose of this study was to examine how capital expenditure in district and city governments in East Java during 2017-2013 was influenced by local own-source revenues, balancing funds, budget surplus financing, and special allocation funds. This research was conducted quantitatively using secondary data from the official website of DJPK, namely the APBD of each district or city in East Java. Purposive sampling was used in the IBM SPSS 25 software analysis tool for sampling. The partial test results (t test) show that capital expenditure is significantly influenced by local own-source revenue, balancing funds, SiLPA, and special allocation funds. Simultaneous test results (f test) show that capital expenditure is significantly influenced by Budget Financing Surplus, Balancing Funds, Regional Original Revenue, and Special Allocation Funds.